Synthesis, structural characterization and magnetic properties of the monoclinic ordered double perovskites BaLaMSbO6, with M = Mn, Co and Ni - Blanco, M. Cecilia (2014)
Fil: Blanco, M. Cecilia. Universidad Nacional de Córdoba. Facultad de Ciencias Químicas. Departamento de Fisicoquímica; Argentina.